The importance of ownership II - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Our second report comes from The Gambia, where Ismaila Senghore spoke to Fatou Sarr, a training officer at the Promotion Centre of the Village Indigenous Savings and Credit Associations, commonly called VISACAs. He discovered that the associations had a strong sense of ownership, not least because all the staff in the credit offices were recruited in the villages.